Signal correction for combinational automation devices on the basis of Boolean complement with control of calculations by parity - V. V. Sapozhnikov; Vl. V. Sapozhnikov; D. V. Efanov (Informatika)
Simpler than known structure of the system with error correction in calculations is proposed based on duplication and triplication of blocks with majority principle of choosing the values of signals. It is advisable to use the new fault-tolerant structure for automation devices with combinational logic. In fault-tolerant structure synthesis, the parity method is used to establish the fact of a fault in the main logic unit and the logical complement method is used determine incorrectly calculated output functions and to generate signals for their correction. The method also allows to adjust the values of incorrectly calculated functions. Structural diagram and description of error correction system are given. The synthesis algorithm of control equipment is described with minimization of the technical implementation complexity. The experiment results with control combinational circuits are given, confirming the high efficiency of proposed system structure with error correction.